Growth and welfare maximization in models of public finance and endogenous growth - Florian Misch; Norman Gemmell; Richard Kneller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper evaluates the trade-off between growth and welfare maximization from two perspectives. Firstly, it synthesizes and extends endogenous growth models with public finance to compare growth and welfare maximizing tax rates. Secondly, it examines the distinct model outcomes in terms of their growth rates and welfare levels. This comparison highlights the range of trade-offs: the growth maximizing tax rate can be above, below, or equal to the welfare maximizing equivalent. We find however that even relatively large differences in growth and welfare maximizing tax rates translate into relatively small differences in growth rates, and, in some cases, welfare levels.
urn:nbn:de:bsz:180-madoc-31910
Keywords: E62; H21; H50; O40; 330; Economic Growth; Productive Public Spending; Optimal Fiscal Policy